CHOOSING AN APPROPRIATE CONTINGENCY SUM ESTIMATING METHODS FOR HIGHWAY CONSTRUCTION PROJECTS IN NIGERIA: A LITERATURE REVIEW - Abdul Hamid, Razali; Kehinde, Fabi Jonathan (PLANNING MALAYSIA, 2017)
In order to establish a gap to be filled in a particular field, there is a need to gather information that allows the researcher to identify and analyse the current state of researches on the topic. Contingency sum estimation for projects plays an important role for inclusion for risk taken by the contractor on the bid amount. This is good in order to meet project objectives (cost, time, quality, health and safety, and environment). The main function of contingency sum is to cater for variations that arise during the construction phase of projects. The aim of the study is to identifying and examine the various methods for estimating contingency sum for projects with a view to propose an appropriate method which will be suitable for a specific project in order to increase accuracy and reduce cost overrun. A literature review of selected papers (journals, conference proceedings and theses) on contingency estimation was carried out. The major findings from this study is that most studies were carried out on building projects while few were carried out on highway projects. From the analysis carried out, no single method of estimating has been effective for all types of projects. These methods of estimating contingency sums have developed over the years as a result of shortcomings of one method after the other. It is therefore recommended that peculiarity of each project, ease of using each of the methods and accuracy of the estimates needed should be the basis of choosing method of estimating contingency sum.